Disparidades étnico-culturais na Perturbação Afetiva Bipolar: comparando afrodescendentes e caucasianos - Elsa Baptista Mendes (2022)
Bipolar Affective Disorder (BAD) is a recurrent and chronic mood disorder with multifactorial etiology. It is one of the most common psychiatric disorders, being associated with elevated risk of suicide and a high socio-economic burden. Even though was described above about the manifestations, natural history, and treatment of BAP are broadly generalizable, some studies indicate important racial-ethnic differences in the expression of BAP and that they may condition a correct identification and treatment of the disease. The present work aims to identify and characterize ethnic differences between Afro-descendants and Caucasians diagnosed with BAD, regarding clinical presentation, diagnosis, therapy, and suicide rates. The present work highlights the importance of taking in consideration sociocultural factors, which may influence the clinical presentation and therapeutic approach to BAD.